(untitled) (Педагогіка вищої та середньої школи, 2008)
The phenomenon of professional self-realization, the conditions of preparation of the teacher to self improvement are investigated in the article. The characteristics of organizational-pedagogical system of formation of mechanisms of professional self-realization reveals is represented.